2011
DOI: 10.1371/journal.pone.0018733
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Auditory Neuron Survival Following Cell-Based BDNF Treatment in the Deaf Guinea Pig

Abstract: Exogenous neurotrophin delivery to the deaf cochlea can prevent deafness-induced auditory neuron degeneration, however, we have previously reported that these survival effects are rapidly lost if the treatment stops. In addition, there are concerns that current experimental techniques are not safe enough to be used clinically. Therefore, for such treatments to be clinically transferable, methods of neurotrophin treatment that are safe, biocompatible and can support long-term auditory neuron survival are necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 62 publications
0
59
1
Order By: Relevance
“…Accordingly, a gradual age-related loss of BDNF in the cochlea, as previously shown to occur in the third life span in rats and gerbils , or altered BDNF levels in psychiatric and neurodegenerative disorders (Lu and Martinowich, 2008;Krishnan and Nestler, 2010;Pardon, 2010), may be discussed in the context of altered loudness perception that has been described in these diseases (Frisina, 2009;Aznar and Knudsen, 2011). Finally, the current ideas to propose BDNF as a promising future therapeutic for hearing deficits (Pettingill et al, 2011) may be revisited in the context of the present study.…”
Section: Ko Micementioning
confidence: 97%
“…Accordingly, a gradual age-related loss of BDNF in the cochlea, as previously shown to occur in the third life span in rats and gerbils , or altered BDNF levels in psychiatric and neurodegenerative disorders (Lu and Martinowich, 2008;Krishnan and Nestler, 2010;Pardon, 2010), may be discussed in the context of altered loudness perception that has been described in these diseases (Frisina, 2009;Aznar and Knudsen, 2011). Finally, the current ideas to propose BDNF as a promising future therapeutic for hearing deficits (Pettingill et al, 2011) may be revisited in the context of the present study.…”
Section: Ko Micementioning
confidence: 97%
“…171 Another study that combined cell-based gene transfer with alginate technology, had demonstrated the survival effects on auditory neurons of encapsulated BDNF-expressing Schwann cells. 182 Such transplanted cells, encapsulated in a biocompatible matrix, would be protected against strong immune responses, and this would allow the patients to avoid using toxic immunodepressants, thus minimizing the associated risk of transplant rejection. Without a doubt, osmotic minipump, gene therapy, stem cell therapy, and cochleostomy are hopeful steps toward successful treatment of the degeneration of SGCs in the inner ear and the loss of hearing.…”
Section: Cell-based Bdnf Deliverymentioning
confidence: 99%
“…Schwann cells, which are capable of expressing BDNF, have been effectively transplanted into the subretinal space of RCS rat strains 105 and to the guinea pig's cochlea. 182 However, viral vector and cell-based therapy are still limited by surgical technique and human immune system. As a promising solution to protect cells from rejection and tumorigenicity, cell transplantation and gene transfer, combined with encapsulation technologies, has been suggested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the promise of NT therapy to rescue SGNs after SNHL has yet to be realized, and effective and safe drug administration strategies for application in the inner ear remains elusive. The use of cell-based therapies provides a clinically viable NT delivery technique that is less susceptible to adverse side effects than pump-based delivery methods [21][22][23]. In the present study, choroid plexus cells (NTCells, Living Cell Technologies, Auckland, New Zealand), which produce and release a cocktail of NTs [24], were encapsulated in biocompatible alginate and implanted into the neonataldeafened cat cochlea in combination with a cochlear implant electrode array.…”
Section: Introductionmentioning
confidence: 99%